2012
DOI: 10.1111/j.1467-856x.2011.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

The Courts and Devolution in the UK

Abstract: The courts have hitherto played a remarkably limited role in the working of devolution in the United Kingdom. In this respect, the UK has been an exception to practice in most federal or decentralised systems, where the courts have tended to assume a prominent role in adjudicating intergovernmental disputes. This article examines whether political congruence contributed to this minimal role for the courts in IGR. It argues that additional factors are also at play: the limited role accorded to lawyers and legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These views were not necessarily based on any empirical assessment of the contemporaneous policy context and operation. Legislation in Scotland had always remained separate since the Act of Union (Trench, 2012). Since 1999, a new period of institutional stabilisation has begun.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These views were not necessarily based on any empirical assessment of the contemporaneous policy context and operation. Legislation in Scotland had always remained separate since the Act of Union (Trench, 2012). Since 1999, a new period of institutional stabilisation has begun.…”
Section: Introductionmentioning
confidence: 99%
“…Keating et al, 2009;Cairney, 2011; and have demonstrated that relationships have not been adversely affected by devolution whilst policy communities have adapted to meet any changes. Trench (2012) argues that this is because devolution has been more administrative than political in its character and the division of responsibilities has been straightforward.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in a federation, the new UK Supreme Court cannot test the legality of UK parliamentary acts with the Acts granting selfrule to the devolved territories, but it can test the compliance of devolved legislation with these Acts (Hazell 2006;Trench 2012). On the other hand, self-rule to the devolved territories was subject to a popular referendum, and by convention the UK Parliament does not amend the Acts on the basis of which devolution was granted without the approval of a concurrent majority in the affected devolved legislature.…”
Section: Neither Federal Nor Unitary: the Uk's Evolution From A Uniomentioning
confidence: 99%